Program Bimbingan Belajar dalam Meningkatkan Pemahaman dan Minat Belajar Siswa di Pekon Tapak Siring Kecamatan Sukau Kabupaten Lampung Barat - Awandi, Hafizh; Alfatih, Nanda Karunia; Nugroho, Rizky Teguh; Athaya, Syifa; Umamit, Nurulla Beliyana; Nabila, Laini; Premana, Ketut Sudire (Research and Social Study Institute (RESSI), 2023)
Education is a very important aspect in every country to ensure the preservation of the nation's life. Students, as the successors of the nation who are at the forefront, must be able to carry out the tri dharma of higher education, namely in the form of education, research and community service. As a form of student service to the community, the University of Lampung Real Lecture Work (KKN) Period 1 of 2023 was held. In carrying out this KKN, the Tapak Siring 1 group held a work program entitled